SEMANGAT REFORMASI DAN IMPLIKASINYA DALAM MENGATASI KRISIS DEMOKRASI INDONESIA - Leonardus Gandi; Aurelius Armat (PT PUBLIKASI INSPIRASI INDONESIA, 2025)
This article analyzes the significance of demands for reform in overcoming Indonesia's democratic crisis. To analyze this problem, the author uses a qualitative descriptive method on data collected through literature studies. The author tries to find literature related to the title of this scientific paper. Based on the author's research from various literatures, the negative trend of Indonesia's democracy index is due to the rise of oligarchs in the current body of power. Oligarchs are representatives of individual interests. How to overcome this? According to the author, returning to the demands of the reformists can be a way out in addressing the existence of oligarchs in the body of power that is the embryo of the decline of the Indonesian democracy index. The demands of the reformists, especially the demands of Suharto and his cronies, have significance in overcoming the power of oligarchs in Indonesia. This is because the oligarchs who live in power today are an extension of the oligarchs of the new order. They are present through the phenomenon of free hitchhiking. The demands of the reformasi have significance in stemming the oligarchs and restoring the dignity of Indonesian democracy.